PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DI PT BPR INDOBARU FINANSIA - wani, Sari; Mardika, Nanda Harry (LPPM Universitas Putera Batam, 2021)
This study aims to examine the effect of facilities and service quality on customer satisfaction at PT BPR Indobaru Finansia in Batam. This study uses a quantitative approach and nonprobability sampling techniques with purposive sampling method. The data collection technique used a questionnaire with a Likert scale which was filled in by 171 respondents. Data analysis used SPSS version 25. The results of the facility variable test were obtained with tcount (6.565)> t table (1.653) and a significance value of 0.000 f table 3.05 and a significant value of 0.000 or less than 0.05 (F. Sig 0.000 <α 0.005). So it can be concluded that the facilities and service quality partially and simultaneously have a significant effect on customer satisfaction at PT BPR Indobaru Finansia in Batam. The test results of the coefficient of determination have 51.3%. The remaining 48.7% is influenced by other variables not in this study.